1 GHz Pentacene diode rectifiers enabled by controlled film deposition on SAM-treated Au anodes - Kang, C; Wade, J; Yun, S; Lim, J; Cho, H; Roh, J; Lee, H; Nam, S; Bradley, D; Kim, J; Lee, C (Wiley, 2015)
Pentacene diodes with 2,3,4,5,6-pentafluorobenzenethiol-coated Au anodes show high current densities of 100 A cm−2 at 3 V with rectification ratios of 107. Using such diodes in rectifier circuits allows an output voltage of 3.8 V to be achieved from a 10 V sinusoidal input at 1 GHz.